The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.31557/apjcp.2019.20.9.2841
|View full text |Cite
|
Sign up to set email alerts
|

PIK3CA and PTEN Genes Expressions in Breast Cancer

Abstract: The molecular biomarkers, and their correlation with pathological parameters are very important for diagnosis, prognosis, predictive utility, management, and prevention of breast cancer (Patani et al., 2013). The phosphatidylinositol-3-kinase (PI3K) pathway is an important signaling pathway in cells and is involved in essential cellular functions such as metabolism, proliferation, survival, motility, and growth and plays a main role in development and progression of breast cancer (Engelman et al., 2006; Boyaul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 26 publications
1
5
0
Order By: Relevance
“…Third, from our pairwise and network meta-analysis, we found that the most effective PI3K inhibitors may be alpelisib and buparlisib. Analogous results have been obtained in some published studies [ 33 , 34 ], and the safety of the above two agents could also be tolerated.…”
Section: Discussionsupporting
confidence: 84%
“…Third, from our pairwise and network meta-analysis, we found that the most effective PI3K inhibitors may be alpelisib and buparlisib. Analogous results have been obtained in some published studies [ 33 , 34 ], and the safety of the above two agents could also be tolerated.…”
Section: Discussionsupporting
confidence: 84%
“…Given the intra-tumor heterogeneity of MMR protein expression in HR+ breast cancer, the reliability and reproducibility of complementary and/or surrogate biomarkers have been investigated by several research groups. Recently, the assessment of phosphatase and tensin homolog (PTEN) expression, a key tumor suppressor gene mainly involved in DNA repair, apoptosis, and cell survival, was suggested as a complementary biomarker to pre-screen MMR status in breast cancer [ 30 , 68 ]. According to this workflow, the positive predictive value of PTEN retained status for pMMR ranged from 94.6 % in HR+ tumors to 100 % in HER2-enriched and HR − breast cancers.…”
Section: Mismatch Repair Testing: Focus On Hr+ Breast Cancermentioning
confidence: 99%
“…The Pik3ca gene is one of the most frequently mutated genes in breast cancer, which leads to PI3K activation (Dong et al, 2021). Recently, PI3K inhibitors can be used as a strategy for cancer treatment alone or combined with other strategies of cancer therapy (Alowiri et al 2019). Herein, treatment with Chia and Quinoa nanocapsules showed a signi cant decrease in Pik3ca expression suggesting their capability to inhibit the PI3K pathway.…”
Section: Discussionmentioning
confidence: 99%